Gd and Zr Co-Doped BiFeO3 Magnetic Nanoparticles for Piezo-Photocatalytic Degradation of Ofloxacin - Xuan Liu; Jie Chao; Feifei Guo; Liangliang Chang; Xinyang Zhang; Wei Long; Zengzhe Xi (Nanomaterials)
Addressing the limitations of poor piezoelectric photocatalytic activity and insufficient magnetic recovery in pure BiFeO3 nanoparticles, Gd and Zr co-doped BiFeO3 nanoparticles were synthesized via the sol-gel method. The structural characterization revealed a rhombohedral-to-orthorhombic phase transition with reduced grain size (~35 nm) and lattice distortion due to dopant incorporation. An XPS analysis confirmed Fe3+ dominance and oxygen vacancy enrichment, while optimized BGFZ9 exhibited enhanced remanent magnetization (0.1753 emu/g, 14.14 increase) compared to undoped BFO. The synergistic piezo-photocatalytic system achieved 81.08% Ofloxacin degradation within 120 min (rate constant: 0.0136 min−1, 1.26 higher than BFO) through stress-induced piezoelectric fields that promoted electron transfer for ·O2−/·OH radical generation via O2 reduction. The Ofloxacin degradation efficiency decreased to 24.36% after four cycles, with structural integrity confirmed by XRD phase stability. This work demonstrates a triple-optimization mechanism (crystal phase engineering, defect modulation, and magnetic enhancement) for designing magnetically recoverable multiferroic catalysts in pharmaceutical wastewater treatment.